2024
DOI: 10.52131/pjhss.2024.v12i1.1921
|View full text |Cite
|
Sign up to set email alerts
|

Association between Work Environment, Work-Family Conflict and Employees’ Turnover Intention through Moderation of Job Experience in Commercial Banking Sector

Abdul Razaque Bhayo,
Naimatullah Shah,
Aftab Ahmed Mangi

Abstract: This study investigated the association between work environments, work family conflict and employee’s turnover intention through moderation of job experience in the commercial banking sector. Intention to leave is an important issue in Pakistan's private sector and is evaluated by management science using a variety of criteria to determine the fundamental cause of employee decision-making. This is quantitative study. It followed convenience sampling techniques and designed sample size on the basis of Krejcie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the commercial banking sector in Pakistan, it was found that a positive work environment and reduced work-family conflict were associated with lower turnover intentions. The study highlighted the moderating effect of job experience on these relationships, suggesting that experienced employees might better handle work stressors (Bhayo et al, 2024). This indicates that strategies to improve work conditions and balance work and family life can be effective in retaining employees in high-stress sectors.…”
Section: Introduction Importance Of Predicting Employee Turnovermentioning
confidence: 85%
“…In the commercial banking sector in Pakistan, it was found that a positive work environment and reduced work-family conflict were associated with lower turnover intentions. The study highlighted the moderating effect of job experience on these relationships, suggesting that experienced employees might better handle work stressors (Bhayo et al, 2024). This indicates that strategies to improve work conditions and balance work and family life can be effective in retaining employees in high-stress sectors.…”
Section: Introduction Importance Of Predicting Employee Turnovermentioning
confidence: 85%